2013
DOI: 10.1097/scs.0b013e31829ad374
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Endoscopic Navigation for the Precise Resection of a Mandibular Condylar Osteochondroma

Abstract: The combined technique reported in this paper could represent a valid minimally invasive approach to the ramus-condyle unit for direct visualization of the medial aspect of the condyle and precise resection of benign tumor located here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Recently, the awareness of minimally invasive surgical techniques to replace traditional larger procedures has attracted interest from an increasing number of surgeons and patients. With endoscopy, direct visual access, along with the capability for illumination and magnification allows for minimal tissue dissection and improved surgical fields [9]. Compared to other fields, the use of endoscopic techniques for exposure, resection, and reconstruction of the condylar disorders are relatively novel approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the awareness of minimally invasive surgical techniques to replace traditional larger procedures has attracted interest from an increasing number of surgeons and patients. With endoscopy, direct visual access, along with the capability for illumination and magnification allows for minimal tissue dissection and improved surgical fields [9]. Compared to other fields, the use of endoscopic techniques for exposure, resection, and reconstruction of the condylar disorders are relatively novel approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with the preoperative virtual planning of the resection extent which relies on merging of different imaging modalities combining the different information of these modalities ( 36 ), this method of navigated tumor resection and tumor mapping harbors promising results. In our study, we showed that with this method there were more R0 resection possible within tumors of the upper jaw compared to the conventional tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, surgical navigation is used to guide osteotomies and to reposition bone segments. Orthognathic procedures that use navigational technology include bimaxillary surgery 37,38,92 , sagittal split ramus osteotomy 100 , high oblique sagittal split osteotomy 56 , intraoral vertical ramus osteotomy 81 , distraction osteogenesis 55,57,66,75,83,84,[95][96][97] , genioplasty 12,54,73,75 , gonioplasty 73 , condyle resection 12,48,58,70 , mandibular angle reduction surgery 69,[74][75][76]79,82 , condyle repositioning after Le Fort I osteotomy 63 , and temporomandibular joint replacement 64 .…”
Section: Applications Of Surgical Navigationmentioning
confidence: 99%
“…3B). Alveolar bone screws can be placed in the outpatient clinic before surgery 48,58,61,68,70 . Next, preoperative CT scanning is performed and the locations of the screws are saved in the preoperative plan.…”
Section: Point Registrationmentioning
confidence: 99%
See 1 more Smart Citation